The effect of heating/ cooling on the upper-branch stability of boundary layer flows over a compliant boundary - Motsa, Sandile S.; Sibanda, Precious; Gajjar, Jitesh S.B. (Computer Assisted Methods in Engineering and Science, 2023)
We investigate the evolution of Tollmien- Schlichting waves in boundary layers in the presence of moderate buoyancy arising from the heating or cooling of a compliant wall. We exploit the multi-deck structure of the flow in the limit of large Reynolds numbers to make an asymptotic analysis of the pertubed flow, along the upper-branch of the neutral stability curve, to derive linear neutral results. These results are discussed and are compared to rigid wall results. Also, a brief parametric study, based on the linear neutral results, is presented and the results are discussed.